Measuring Organizational Climate: an evaluation proposal for psychologists in the industrial-organizational field - Chirio Aldazabal, Diego Bernardo (2022)
The purpose of this paper is to build and review the psychometric properties of the Brief Work Climate Scale (EBCL), therefore, an instrument comprised of 15 items in its initial version was designed, which had a Likert-type response scale with 5 alternatives, of which only 13 items had content-based validity evidence due to an Aiken’s V greater than .80, with probability of statistical significance (p < .05). The final version was applied to two sample groups (n1 = 121; n2 = 126) of employees at the operational level of two companies related to the grocery sales sector in Metropolitan Lima. In the first sample, the exploratory factorial analysis was reviewed with a Pearson correlation matrix, demonstrating the existence of two well-defined models (two oblique factor model and one-dimensional model), the first factor explained 55.4% of the accumulated variance and the second 49.1%. Confirmatory factor analysis was performed with the second sample group, in such a way that the two models mentioned above and a bifactor model were compared, identifying that the goodness-of-fit indices were not satisfactory to confirm any predominant model; however, there is adequate reliability in the reaction-effect dimension of the worker (α = .91, ω = .90) and company factors (α = .82, ω = .86); as well as for the one-dimensional model (α = .92, ω = .94). The results show that the EBCL Scale has adequate evidence of psychometric properties.